The high social and environmental costs of food in Kenya detailed in new research - Kibui, Rachel (CGIAR System Organization, 2024)
The mention of food costs brings to mind the prices consumers pay, along with expenses producers have for seeds, labor, transport, and others. However, the true cost of food extends beyond these visible factors, encompassing deeper, often overlooked costs. IFPRI’s Research on True Cost of Food in Kenya